Subcutaneous Fat Thickness and Superficial Surgical Site Infectionin Patients Undergoing Open Appendectomy: An ObservationalStudy - Thapa, Kaushal Samsher; Joshi, Anip; Aryal, Rishikant; Maharjan, Suresh; Yadav, Saurav Suman; Shah, Arina (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Appendectomy is done for the treatment of acute appendicitis. Surgical Site Infection is a common postoperative complication. Most of the time, body mass index is measured to determine the presence of obesity. Still, it cannot predict adiposity at the incision site, so subcutaneous fat, which can be measured easily at the incision site, can be a better predictor. This study aimed to find a correlation between subcutaneous fat thickness and superficial surgical site infection in patients undergoing emergency open appendectomy.Methods: This prospective observational study was done from July 2023 to July 2024, including 118 cases with a diagnosis of uncomplicated appendicitis. Ethical approval was taken from the Institutional Review Board (Ref: 534/2080/81). Data were collected as per the proforma and maintained in Microsoft excel. Statistical Package for the Social Sciences version 26 and Pearson correlation were used for statistical analysis.Results: Among 118 patients included, 11 (9.30%) had superficial surgical site infection, which was higher among female patients 6 (12%). The calculated cut-off subcutaneous fat thickness was 2.05 cm in our study. The estimated positive predictive value was 16.99% and the negative predictive value was 98.17% for subcutaneous fat in predicting infection. The receiver operating characteristic curve showed an area under the curve of 0.75, indicating that subcutaneous fat can be used as one of the predictors of superficial SSI infection. Conclusions: Patients with increased subcutaneous fat thickness at the incision site had a higher incidence of surgical site infection. This concluded that increased subcutaneous fat thickness increases the risk of superficial surgical site infection, and that local adiposity at the site of the incision is a good predictor of surgical site infection.